Inexact Design- Beyond Fault-Tolerance. - Anthes, Gary (Communications of the ACM, 2013)
The article discusses the design of computer hardware that is intended to be inaccurate in order to increase speed and efficiency and decrease energy usage, a version of fault-tolerance developed by computer scientist Krishna Palem from Rice University. Computer researcher John von Neumann's attitude toward logic errors is mentioned, as well as application-specific integrated circuits (ASICs) developed at Nanyang Technological University, and the design of semiconductors. Moore's Law, technological trends, and relevancy ranking of information are discussed.